Intranasal insulin and postoperative delirium in adult surgical patients: a meta-analysis and systematic review of randomized controlled trials - Zhang, Li-cai; Song, Jian-li; Qiu, Li-quan; Li, Qiang; Yu, Xuan; Lu, Bin; Chen, Guan-yu (Frontiers in Medicine, 2025)
IntroductionThe efficacy and safety of intranasal insulin (INI) for preventing postoperative delirium (POD) remain uncertain.MethodsWe searched PubMed, Web of Science, Cochrane Library, Embase, and registers from inception to July 1, 2025, for randomized controlled trials (RCTs) enrolling adult surgical patients that compared INI with control (saline) investigating the efficacy of INI for POD prevention. The risk of bias was assessed using the revised Cochrane Risk of Bias tool (RoB 2), and the certainty of evidence was evaluated with the GRADE framework. Primary and secondary outcomes were POD incidence and a comprehensive set of secondary measures (including cognitive scores, hypoglycemia rates, pain scores, and inflammatory markers), respectively.ResultsA meta-analysis of 7 randomized trials (n = 765) showed that INI significantly reduced the incidence of POD within 3 days postoperatively (RR = 0.35; 95% CI: 0.26–0.46; P < 0.001; I2 = 0%) and improved cognitive recovery (MMSE mean difference = 0.99; 95% CI: 0.52–1.47; P < 0.001; I2 = 1.7%). INI also reduced early postoperative interleukin-6 (IL-6) levels without affecting the incidence of hypoglycemia or pain scores.ConclusionINI may protect perioperative cognitive function, reduce POD incidence within 3 days postoperatively, and alleviate postoperative inflammation without increasing hypoglycemia risk. However, larger-scale, randomized, multicenter trials are needed to confirm clinical efficacy and establish optimal protocols.Clinical trial registrationThe protocol for this meta-analysis is available in PROSPERO (CRD42024614995).